Successful Treatment of Mesentric Panniculitis by Using Small Doses of Ster-oid for a Short Period: Case Report - Ibrahim, Olla A M; Alwamy , Salah M; Alhaen, Enas M (Al-Mukhtar Journal of Sciences, 2019)
Mesenteric panniculitis is a rare inflammatory disease affecting the adipose tissue of the mesentery and colon. Less than 300 cases had been reported worldwide by 2016. There is a lack of universal consensus regarding management guidelines, and the cases are treated on an individual basis. Therefore, successful management of this case by using small doses of steroid would empower clinician's experience of how to manage such cases. A 62-year-old female has a known case of hypertension and bronchial asthma, presented by exacerbation and acute abdominal pain. Lab results revealed a mild elevation in inflammatory markers and bilirubin. Computed tomography showed typical findings of mesenteric panniculitis. The case was managed by a small steroid dose for a short period till the symptoms were controlled, thereafter the dose was safely tapered gradually. A follow-up scan revealed complete resolution of the disease. The literature reports different types of therapy, ranging from observation to medical therapy and even surgical interventions. Reported cases were treated by different protocols using steroids, cytotoxic drugs, antibiotics and radiotherapy has been used in some cases, Reporting this case would raise awareness of how symptoms would present, what is the essential diagnostic tool to be used, and highlighting the possibility of using a small dose of steroid to successfully manage such cases.